A new Archipsocidae (Psocodea: Psocomorpha) from the middle Miocene Zhangpu amber, China - Jouault, Corentin; Zhuang, Yu-Hui (Palaeoworld, 2025)
A new species of Archipsocidae, Archipsocus palaeosinicus n. sp., is described and illustrated from the middle Miocene Zhangpu amber. This taxon possesses all the synapomorphies of the Archipsocidae family and can be confidently classified within the genus Archipsocus due to its exceptional preservation, which allows for the detailed examination of the morphological traits used to define the genus and its species. Archipsocus palaeosinicus n. sp. is distinguished from other species of Archipsocus, inter alia, because of the first flagellomere that is shorter than the pedicel, a relatively flat antennal diagram, a unique arrangement of marginal setae on its fore- and hindwings, distinct venation patterns in both wings, and hindlegs with the first tarsomere longer than the second. The discovery of this species indicates that the genus Archipsocus likely had a broad distribution, with representatives in both China and Mexico during the Miocene.